Macroeconomic and Bank-Specific Factors Influencing Cost Efficiency in Islamic Banking: Evidence from Indonesia - Purnomo, Rino; Isro, Arsan; Munir, Misbahul; Madqur, Madqur (Syari'ah Economics, 2025)
The dual banking system in Indonesia intensifies competition between conventional and Islamic banks, impacting operational costs and income. From 2015 to 2024, the BOPO (Operational Cost to Operational Income) ratio of Islamic banks fluctuated between 97% and 76%, reflecting inefficiencies influenced by internal and external factors. This study examines the determinants of BOPO in Indonesian Islamic banking using quantitative methods, specifically multiple linear regression analysis of monthly data (2015–2024). The independent variables include bank-specific metrics (Capital Adequacy Ratio/CAR and Return on Assets/ROA) and macroeconomic indicators (BI Rate, inflation, and economic growth). The results indicate that CAR, ROA, BI Rate, and inflation significantly and negatively affect BOPO, suggesting that higher capital adequacy, profitability, and interest rates, along with controlled inflation, improve operational efficiency. Conversely, economic growth shows no significant impact. These findings provide critical insights for Islamic bank managers and policymakers to enhance efficiency through strategic capital allocation, risk management, and macroeconomic stability measures. Keywords: CAR, ROA, BI Rate, Inflation, Economic Growth, and BOPO.